Journal of Diseases - Sandra, Grumelli (Journal of Diseases, 2018)
An editorial introduction to the Journal of Diseases outlines its scope across infectious, chronic, and emerging conditions. It emphasizes integrative research, methodological rigor, and open access to accelerate translation into public health and clinical practice.